The Relationship Between Hormonal Acceptor Knowledgelevels about Implants Contraceptive with the Use Of Implants Contraceptive - ari lindariati; Yustina Ananti; Mia Dwi Agustiani (Jurnal MID-Z (MIDWIFERI ZIGOT), 2023)
The number of implants contraceptives’s acceptors according to the national level, East Java, and in Pacitan is still quite low. At the Tanjungsari Public Health Center, Pacitan, the achievement of the acceptor’s implant contraceptives is also still less than the target. The reasons acceptors don’t choose birth control implants are because they are various, including fear of pain in the installation, not wanting a small surgical method, feeling ineffective because they have to be removed by health workers and others. The purpose of the study was to determine the relationship between the level of acceptor knowledge about implant contraceptives and the use of implants contraceptives at the Tanjungsari Health Center, Pacitan. In this study the design used was descriptive analytical research with a cross sectional research design. Sampling technique using purposive sampling. The samples in the study were 86 acceptors of hormonal contraceptives who visited the Tanjungsari Public Health Center during January-October 2022. Data analysis using chi-square test analysis using the SPSS program obtained test result values = 0.157 or p values > of 0.05 so that Ho was accepted and Ha was rejected, meaning that there was no relationship between the hormonal acceptor's level of knowledge about implant contraceptives and the use of implants contraceptives at the Tanjungsari Health Center, Pacitan. There is no relationship between the hormonal acceptor's level of knowledge about implant contraception and the use of implants contraceptives at the Tanjungsari Health Center, Pacitan in 2022